Penggunaan Teknologi Informasi Dalam Penegakan Hukum Pada Bidang Sistem Politik (International Forum of Researchers and Lecturers, 2024)
This research aims to evaluate the response of law enforcement officials to 4,444 cases of criminal acts of gambling via electronic media in Indonesia. The approach in this research refers to legal norms contained in legal regulations and literature, involving normative legal analysis and a qualitative approach. The research results show that law enforcement policies against criminal acts of gambling via electronic media need to be regulated and integrated in the legal field, as well as developing new laws. The use of these legal instruments is considered important to support development in various sectors, which depends on development needs, community legal awareness, and their views on behavioral assessment. In imposing sentences on perpetrators of gambling crimes, a general minimum criminal system and a special maximum criminal system are applied. However, in this system, judges do not have complete freedom to determine the appropriate type of punishment, but must follow the provisions for criminal intimidation regulated in law. In conclusion, to eradicate criminal acts of gambling via electronic media in Indonesia, it is necessary to increase the quality and quantity of Information Technology and Electronic Equipment (ITE) investigators at the National Police and National Police Headquarters levels, especially because law enforcement officers face difficulties identifying online gambling brokers who use fake identities and catch them effectively.